Kepemimpinan Technopreneur Dalam Bidang Farmasi: Studi Pengambilan Keputusan dan Integrasi Nilai - Nilai Syariat Islam Dalam Pengolahan Usaha - Frya RahmanDanny; Jaira Jacquitta Putri; Rifa Husnul Khotimah; Mochammad Fadhlani Salam (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study aims to describe the characteristics of Muslim technopreneur leadership, analyze the decision-making process, and examine the implementation of Islamic values in managing a Sharia-based pharmaceutical business. The research uses a descriptive qualitative approach with a case study of Apotek Fernanda, owned by Mrs. Yelni Erita, located in Tembilahan, Riau. The results of the study show that Muslim technopreneur leadership is reflected in the integration of Islamic values such as honesty, trust, responsibility, and blessings, which are applied as the main principles in running the business. This leadership emphasizes the importance of personal character in line with Islamic teachings, where every decision made should be based on moral and spiritual principles. The decision-making process is carried out carefully, especially with spiritual considerations. Mrs. Yelni Erita often conducts istikharah to seek guidance from Allah before making important business decisions. Additionally, consultations with the team and evaluation of maslahat (benefit) are part of the decision-making process to ensure that the steps taken bring the greatest benefit, not only for the business but also for the community at large. This approach does not only prioritize profit but also considers the social and spiritual well-being of all parties involved. In managerial practices, the implementation of Islamic values is reflected in the selection of halal products, ethical service systems, and work relationships based on fairness and transparency. Apotek Fernanda provides services while upholding these principles, ensuring that the products sold meet halal standards and offering customer-oriented services. The application of these Sharia principles not only meets the needs of an increasingly discerning and critical market but also brings positive economic and spiritual impacts to the community. The findings show that entrepreneurship in the pharmaceutical field can be developed competitively while adhering to Sharia principles, providing sustainable profits and positive impacts on the broader community.